Executive compensation and firm performance: evidence from the UK charities - Ndoro, Girlie (2012)
The past two decades have seen extensive research on governance structures of the firm, executive compensation and performance. However, most of these studies are in the context of profit-making organisations with relatively very little attention being given to this subject in respect of non-profit making organisations. This study examines the determinants of executive compensation and firm performance in charities. Specifically this study attempts to answer the following questions: What are the main determinants of CEO compensation in the UK Charities? What performance measures do the UK Charities use? What are the factors that influence performance in the UK charities? Using both quantitative and qualitative methodologies, the study reports a number of interesting findings. Regarding the executive compensation, the study finds that organisational size, CEOs qualification and CEO’s tenure have a positive bearing on executive pay. However, the results suggest that the sector of the organisation and CEO duality have no impact while and CEO experience had significantly negative relations with CEO pay. Turning to the performance measures, it was found that five performance measures categories are used by the UK charities, namely, financial, the customer; the internal business process, benchmarking and learning and innovation. To get deep insights into performance, the study examined the managers’ opinions on the factors influencing performance. However, CEO pay and the sector of operations have a statistically negative influence on performance. The results indicated that four factors, namely, board size, board independence, CEO pay and sector of operations, have statistically significant influences on the overall performance of the UK charities. The also results suggest that board size and board independence have positive and significant influence on performance. In terms of individual performance measures, the size of the board has a positive and significant influence in respect to financial, customer, internal business and overall performance. The results also indicate that board independence has an influence on financial performance, internal business, benchmarking and overall performance. On the contrary, benchmarking has a positive, but not significant, relationship with CEO pay. This relationship is not surprising, as it supports the social comparison and equity theory. The results also show that the gender of the CEO appears to have a positive, but not significant, impact on the CEO’s performance, with the exception of innovation and learning.